2014
DOI: 10.1080/08870446.2014.896463
|View full text |Cite
|
Sign up to set email alerts
|

Early attachment quality moderates eating disorder risk among adolescent girls

Abstract: Results delineate one way early attachment quality may contribute to EDs among some adolescent girls, and support recent efforts to incorporate relational components into obesity and ED prevention programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 43 publications
1
32
0
2
Order By: Relevance
“…The severity of drive for thinness, body dissatisfaction, bulimia, and binge and purge symptoms were related to the degree of attachment insecurity in the SM group, which is in line with previous studies that evidenced the association between lower attachment security and stronger ED symptoms (Broberg et al, 2001) dysfunctional eating attitudes and behaviors, and an increased risk of EDs (Milan & Acker, 2014). The stronger association between ED symptoms and adult attachment dimensions then parental bonding features in SM individuals may suggest that SM adults consider their partner or close peer relationships as primary attachments rather than their parents.…”
Section: Characteristics Of Sine Morbo Individualssupporting
confidence: 78%
See 2 more Smart Citations
“…The severity of drive for thinness, body dissatisfaction, bulimia, and binge and purge symptoms were related to the degree of attachment insecurity in the SM group, which is in line with previous studies that evidenced the association between lower attachment security and stronger ED symptoms (Broberg et al, 2001) dysfunctional eating attitudes and behaviors, and an increased risk of EDs (Milan & Acker, 2014). The stronger association between ED symptoms and adult attachment dimensions then parental bonding features in SM individuals may suggest that SM adults consider their partner or close peer relationships as primary attachments rather than their parents.…”
Section: Characteristics Of Sine Morbo Individualssupporting
confidence: 78%
“…Mothers of SM ones reported higher security than mothers of anorexic patients, and were less avoidant than mothers of bulimic patients (Tereno et al, 2008). The quality of parental attachment can lead to dysfunctional eating attitudes; it may influence the quantity and quality of food eaten and moderate the risk of EDs (Faber & Dubé , 2015;Milan & Acker, 2014). From the opposite direction of influence, both the physical and psychological proximity needs can be increased in patients after the onset of EDs.…”
Section: Attachment and Eating Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Kerns ve Brumariu da, benzer şekilde böyle bireylerin, duygu yönetiminde sorun yaşadıkları için akranlarla olan ilişkilerinin bozulduğunu ve bu durumun da uzun vadede anksiyeteyi arttırabileceğini bildirmiştir 33 . Güvensiz bağlanmanın ergenlik döneminde yeme bozukluğuna da yol açabileceğine dair çalışmalar vardır 34,35 .…”
Section: Güvensiz Bağlanma İle İlişkili Yetişkin Ruhsal Sorunlarunclassified
“…Importantly then, four of the longitudinal and prospective studies (Allen et al, 2009;Nicholls & Viner, 2009;Tanofsky-Kraff et al, 2011;Zerwas et al, 2014) lend equivocal support to the predictive validity of maternally reported childhood anxiety relative to eating disorder symptoms. One study (Milan & Acker, 2014) also found that an insecure attachment style mediated by an elevated pubertal BMI predicted eating disorder symptoms .…”
Section: Anxiety Disorders and Eating Disordersmentioning
confidence: 99%